Latin America: In search of security beyond geopolitics - Eguizábal Mendoza, Cristina (2012)
Historically geopolitics in the Western hemisphere has been determined by the United States’ security interests. The U.S. national security interests have in turn been defined in response to the U.S. interests as a global power and the balance of forces established at a given time. The Latin American countries’ margins of autonomy have been inversely proportional to [perceived U.S. power in the world. We focus our analysis in the post Cold War period. In the first section we situate the Western Hemisphere in the global context of unipolarity following the collapse of the Berlin Wall. In a second section we analyze the recent changes in Latin American foreign policies as a consequence of recent changes in the global balance of power. Thirdly we discuss the evolving content of the concept of security and finally we go over the old and new threats faced by the Latin America countries.